Mood Disorders Are Associated with Increased Perioperative Opioid Usage and Health Care Costs in Patients Undergoing Knee Cartilage Restoration Procedure. (March 2022) - Stone, Austin V.; Murphy, Meredith L.; Jacobs, Cale A.; Lattermann, Christian; Hawk, Gregory S.; Thompson, Katherine L.; Conley, Caitlin E. W.
Objective: To identify the prevalence of mood disorder diagnoses in patients undergoing cartilage transplantation procedures and determine the relationship between mood disorders, opioid usage, and postoperative health care costs. Design: Patients with current procedural terminology (CPT) codes for osteochondral autograft transplantation (OAT), osteochondral allograft transplantation (OCA), and autologous chondrocyte implantation (ACI) were identified in the Truven Health Marketscan database (January 2009-September 2014). Patients were grouped based on having a preoperative mood disorder diagnosis (preMDD). Preoperative opioids, postoperative opioids ≥90 days, and health care costs within the year postoperative were compared for those with and without mood disorders. Costs were analyzed, adjusting for preoperative cost, sex, age, and opioid usage, for those with and without mood disorders. Results: A total of 3, 682 patients were analyzed (ACI: 690, OAT: 1, 294, OCA: 1, 698). A quarter of patients had preMDD (ACI: 25.4%, OAT: 20.6%, OCA: 22.7%). Postoperative opioid use was more prevalent in preMDD patients (OAT: 37.1% vs. 24.1%, P < 0.001; OCA: 30.4% vs. 24.8%, P = 0.032; ACI: 33.7% vs. 26.2%, P = 0.070) (odds ratio [OR] ranged from 1.29 to 1.86). First-year postoperative log-transformed costs were significantly greater for preMDD patients (ACI: 7, 733 vs. 5, 689*, P = 0.012; OAT: 5, 221 vs. 3, 823*, P < 0.001; OCA: 6, 973 vs. 3, 992*, P < 0.001; *medians reported). The estimated adjusted first postoperative year cost increase for preMDD OCA patients was 41.7% ( P < 0.001) and 28.0% for OAT patients ( P = 0.034). There was no statistical difference for ACI patients ( P = 0.654). Conclusion: Cartilage transplantation patients have a high prevalence of preoperative mood disorders. Opioid use and health care costs were significantly greater for patients with preoperative mood disorder diagnoses. Level of Evidence: Level III, retrospective therapeutic study.